Implications for patients waiting for a kidney transplant of using the calculated panel reactive antibody (cPRA) - Magriço, R. (2016)
Introduction: Kidney transplant improves survival even in highly‑sensitized (HS) patients. To overcome their disadvantage in accessing transplantation, those with high Complement Dependent Cytotoxic PRA (CDC‑PRA) receive additional points during allocation. Whether this strategy reaches all HS patients and how long they wait for a transplant is largely undetermined. Methods: Patients on our unit’s active wait‑list for kidney transplantation in the year 2014 were analyzed. CDC‑PRA and calculated PRA (cPRA) were recorded. To obtain cPRA, antibodies in the last serum available specific for HLA‑A, ‑B or –DR with an intensity > 1000 MFI were considered. Results: The cPRA values in the population (N=551) were 0% (N=312), 1‑79% (N=118) and ≥ 80% (22%; N=121). Among these groups, the proportion of women (29.5, 55.9 and 61.2%, P<0.001), prior sensitizing events (43.3, 80.5 and 96.7%, P<0.001) and time on dialysis (median of 3.9, 4.1 and 6.0 years, P<0.001) increased with cPRA, respectively. In most of those with a cPRA ≥ 80%, the CDC‑PRA raised no suspicion of HS status (median 0%, P25‑75 0‑8%) and only 35 (28.9%) or 12 patients (9.9%) had a CDC‑PRA in the peak serum higher than 50 or 80%, respectively (cut‑offs needed to obtain additional points during allocation). HS patients by cPRA corresponded to 71% vs 15% of patients waiting for ≥ or <8 years, respectively (P<0.001). Even after exclusion of patients with a CDC‑PRA above 50%, this disproportionate representation remained (58% versus 13%, P<0.001). Conclusion: HS patients as measured by cPRA remained longer on the wait‑list, both in the primary analysis and when excluding those with a CDC‑PRA> 50%. Moreover, only 30% of HS by cPRA patients received the extra points designed to improve their transplantability. We consider that both CDC‑PRA and cPRA should be taken into account when defining HS status.